Targeting of drug-loaded nanoparticles to tumor sites increases cell death and release of danger signals - Alev, Magdalena; Egenberger, Laura; Mühleisen, Laura; Weigel, Bianca; Frey, Benjamin; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph; Janko, Christina (Journal of Controlled Release, 2018)
Innovative strategies fighting cancer by inducing anti-tumor responses from the immune system are urgently needed. Amongst others, chemotherapeutics from the class of the anthracyclines have been shown to induce death of cancer cells with immunogenic features and triggering immunogenic anti-tumor responses. However, the patient's immune system often becomes severely impaired by the unspecific action of these cytotoxic drugs in systemic chemotherapy, preventing any effective immune reactions. To reduce systemic side effects and to accumulate the drug exclusively in the tumor region, we developed an iron oxide nanoparticle-based system for the magnetically targeted delivery of mitoxantrone to the tumor, which has previously proven its long-term therapeutic efficacy in tumor bearing rabbits. Here, we show in vitro that superparamagnetic iron oxide nanoparticles (SPIONs), loaded with the chemotherapeutic drug mitoxantrone, are able to induce cell death with immunogenic features and concomitant maturation of dendritic cells, comparable to the free drug, whereas unloaded nanoparticles are very biocompatible. We conclude that the targeted delivery of mitoxantrone to the tumor region might be a promising possibility to selectively modulate the tumor microenvironment and to locally stimulate immune responses against the tumor. Thus, SPIONs can be used as a platform to specifically bring immunogenic cell death inducers (e.g. mitoxantrone, hypericin, doxorubicin) to the tumor region by sparing the immune system from their toxic effects.
EVALuna2:35474